PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN BOPO TERHADAP CAPITAL ADEQUACY RATIO DENGAN RETURN ON ASSETS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN SYARIAH DI INDONESIA - M Gilang Ramadhan; Marlina Widiyanti; Taufik Saggaf (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2016)
This study aimed to analyze the influence of current ratio, debt to equity ratio, and BOPO of capital adequacy ratio with return on assets as intervening variable in Islamic Banks Company’s in Indonesia on quarterly 2010-2013 period. The population were all Islamic Bank in Indonesia listed on the Indonesia Bank as many as 11 Islamic Banks. The sample is as many as seven Islamic Banks that the result in which using purposive sampling metods. Analysis technique is used path analysis. The results of the study shown that partially Current Ratio is positive and insignificant effect on ROA, DER is positive and significant effect on ROA, BOPO is negative and insignificant effect on ROA, CR, DER, and ROA is positive and significant effect on CAR, BOPO is negative and insignificant on CAR, ROA have mediating effect on relationship between CR on CAR, ROA have mediating effect on relationship between DER on CAR, ROA did not have mediating effect on relationship between BOPO on CAR. Keywords : CR, DER, BOPO, ROA, and CAR